Effect of Hot Isostatic Pressing on Porosity and Mechanical Properties of 316 L Stainless Steel Prepared by the Selective Laser Melting Method - Cegan, Tomas; Pagac, Marek; Jurica, Jan; Skotnicova, Katerina; Hajnys, Jiri; Horsak, Lukas; Soucek, Kamil; Krpec, Pavel (Materials (Basel, Switzerland), 2020)
The manufacturing route primarily determines the properties of materials prepared by additive manufacturing methods. In this work, the microstructural features and mechanical properties of 316 L stainless steel prepared by the selective laser method have been determined. Three types of samples, (i) selective laser melted (SLM), (ii) selective laser melted and hot isostatic pressed (HIP) and (iii) selective laser melted and heat treated (HT), were characterized. Microstructural analysis revealed that SLM samples were formed by melt pool boundaries with fine cellular-dendritic-type microstructure. This type of microstructure disappeared after HT or HIP and material were formed by larger grains and sharply defined grain boundaries. The SLM-prepared samples contained different levels of porosity depending on the preparation conditions. The open interconnected LOF (lack of fusion) pores were observed in the samples, which were prepared with using of scanning speed 1200 mm/s. The blowhole and keyhole type of porosity were observed in the samples prepared by lower scanning speeds. The HIP caused a significant decrease in internal closed porosity to 0.1%, and a higher pressure of 190 MPa was more effective than the usually used pressure of 140 MPa, but for samples with open porosity, HIP was not effective. The relatively high yield strength of 570 MPa, tensile strength of 650 MPa and low ductility of 30-34% were determined for SLM samples with the lower porosity content than 1.3%. The samples after HIP showed lower yield strengths than after SLM (from 290 to 325 MPa) and relatively high ductility of 47.8-48.5%, regardless of the used SLM conditions.
Keywords: selective laser melting; porosity; X-ray computed micro-tomography; tensile strength; hot isostatic pressing; additive manufacturing; 316 L steel